The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/2041-8205/737/1/l2
|View full text |Cite
|
Sign up to set email alerts
|

Radial Velocity Confirmation of a Binary Detected From Pulse Timings

Abstract: A periodic variation in the pulse timings of the pulsating hot subdwarf B star CS 1246 was recently discovered via the O-C diagram and suggests the presence of a binary companion with an orbital period of two weeks. Fits to this phase variation, when interpreted as orbital reflex motion, imply CS 1246 orbits a barycenter 11 light-seconds away with a velocity of 16.6 km s −1 . Using the Goodman spectrograph on the SOAR telescope, we decided to confirm this hypothesis by obtaining radial velocity measurements of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…For the non-linear, least-squared fitting process, we used the Levenberg-Marquardt (LM, hereafter) minimisation algorithm as implemented in the IDL routine MPFIT 1 (Markwardt et al 2009). This algorithm has found widespread applications within astronomy including timing-modeling (Barlow, Dunlap & Clemens 2011). In this routine, partial derivatives for computing the gradient field in a parameter space are calculated from numerical differentiations of model functions.…”
Section: Least-squared Fitting With Mpfitmentioning
confidence: 99%
See 1 more Smart Citation
“…For the non-linear, least-squared fitting process, we used the Levenberg-Marquardt (LM, hereafter) minimisation algorithm as implemented in the IDL routine MPFIT 1 (Markwardt et al 2009). This algorithm has found widespread applications within astronomy including timing-modeling (Barlow, Dunlap & Clemens 2011). In this routine, partial derivatives for computing the gradient field in a parameter space are calculated from numerical differentiations of model functions.…”
Section: Least-squared Fitting With Mpfitmentioning
confidence: 99%
“…The studies by Beuermann et al (2010) and Potter et al (2011) inferred the presence of additional massive objects by explaining the observed timing anomalies with the light-travel time (LTT, hereafter) effect. In the ideal case, the stellar components of an eclipsing binary system are orbiting their common centre of mass with a constant period.…”
Section: Introductionmentioning
confidence: 99%
“…V2051 Oph (AB) b, Qian et al 2015). In particular, the detection of a late-type main sequence star companion to the sdB CS 1246 by Barlow et al (2011b), subsequently confirmed with radial velocity data (Barlow et al 2011a), or other studies like Otani et al (2018), demonstrate the viability of this method in sdB systems. On the other hand, the particular example of V391 Peg b is currently under discussion (Silvotti et al 2018) because of possible non-linear interactions between different pulsation modes that change arrival times (see Zong et al 2018 for a detailed study of amplitude/frequency variations related to non-linear effects).…”
Section: Introductionmentioning
confidence: 62%
“…Stellar pulsations can also serve as accurate clocks for discovering planets (see Schuh 2010). Confirmation of the pulse timing method's ability to find unseen companions has been provided in several cases (e.g., Vinko 1993; Barlow et al 2011), although none of the detected objects were planets. A few substellar and planetary detections have been reported, but without radial velocity confirmation (Silvotti et al 2007;Mullally et al 2008a).…”
Section: Stellar Pulsation Timing For Exoplanet Detectionmentioning
confidence: 98%